2009
DOI: 10.1038/ajg.2009.177
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Pediatric Ulcerative Colitis: A Population-Based Cohort Study

Abstract: Pediatric UC was characterized by widespread localization at diagnosis and a high rate of disease extension. Twenty percent of children had their colon removed after 5 years. The colectomy rate was influenced by disease extension and was associated with the presence of EIMS at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
210
13
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(256 citation statements)
references
References 45 publications
23
210
13
10
Order By: Relevance
“…9 In the process of analysis of data on paediatric UC patients, a family history of IBD was identified as a risk factor for disease progression. 16 We were unable to confirm these findings in our study of adult UC patients. In the course of literature search, we did not find any studies that evaluated factors associated with disease regression.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…9 In the process of analysis of data on paediatric UC patients, a family history of IBD was identified as a risk factor for disease progression. 16 We were unable to confirm these findings in our study of adult UC patients. In the course of literature search, we did not find any studies that evaluated factors associated with disease regression.…”
Section: Discussioncontrasting
confidence: 55%
“…At diagnosis, UC patients presented with the following disease extent: proctitis [199 patients (21.7%)], left-sided colitis [338 patients (36.8%)] and extensive colitis/pancolitis [381 (41.5%)]. During a median disease duration of 9 [4][5][6][7][8][9][10][11][12][13][14][15][16] years, progression and regression was documented in 145 patients (15.8%) and 149 patients (16.2%) respectively. In addition, 624 patients (68.0%) had a stable disease extent.…”
Section: Resultsmentioning
confidence: 99%
“…Gower-Rousseau et al 21 reported that a delay of more than 6 months in diagnosis was associated with an increased risk of extensive disease.…”
Section: Quality-of-life Summarymentioning
confidence: 99%
“…The phenotype of children with VEO-IBD is loosely defined but is usually considered as being more severe than when diagnosed later in life. [17][18] However, most published studies have not been population based but covered patients followed in referral centres, and the incidence and natural history of VEO-IBD are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%